2021
DOI: 10.37929/nveo.927770
|View full text |Cite
|
Sign up to set email alerts
|

Zerumbone induces growth inhibition of Burkitt’s lymphoma cell line via apoptosis

Abstract: Zerumbone (ZER), a natural compound has been extracted from Zingiber zerumbet with known pharmacological activities. The aim was to determine the anti-human Burkitt's lymphoma (Raji) cell effect of ZER. The 3-(4,5-dimethylthiazol-2-yl)-2,5,diphenyltetrazolium bromide (MTT) assay was used to determine cytotoxic effect while the Annexin-V-fluorescein isothiocyanate/propidium iodide-PI flow cytometric assays was used to determine apoptotic effect of ZER on the human Burkitt's lymphoma (Raji) cell (ATCC CCL-86) ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The release of cytochrome C GFP was monitored using time-lapse imaging and fluorescence microscopy. These results also demonstrated that the extrinsic or intrinsic apoptosis pathway is activated by the release of cytochrome C-GFP, following the administration of apoptosis-inducing drugs [23,24].…”
Section: Discussionmentioning
confidence: 59%
“…The release of cytochrome C GFP was monitored using time-lapse imaging and fluorescence microscopy. These results also demonstrated that the extrinsic or intrinsic apoptosis pathway is activated by the release of cytochrome C-GFP, following the administration of apoptosis-inducing drugs [23,24].…”
Section: Discussionmentioning
confidence: 59%
“…Among various anticancer mechanisms proposed, antiangiogenic and modulating intracellular ROS mechanism has also important role, in which immune systems are given opportunity to identify and respond to the tumor cells [14]. ZER, a natural sesquiterpene from edible ginger Zingiber zerumbet Smith, has anti-inflammatory, immunomodulatory, antibacterial [15][16][17], antioxidant, antinociceptive, and anti-proliferation activities against several cancer cells [18][19][20]. Even though, the pharmacological studies had shown the anticancer effects of ZER through the induction of apoptosis on human lung cancer cells [21], the antiangiogenic activity of ZER and its possible anticancer capacity by modulating intracellular ROS have not been clearly evidenced yet.…”
Section: Introductionmentioning
confidence: 99%